2021
DOI: 10.3389/fpls.2021.752648
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Boron Nanoencapsulated in Almond Trees Allows B Movement Within Tree and Implements Water Uptake and Transport Involving Aquaporins

Abstract: Nanotechnology brings to agriculture new forms of fertilizer applications, which could be used to reduce environmental contamination and increase efficiency. In this study, foliar fertilization with nanoencapsulated boron (B) was studied in comparison to an ionic B (non-encapsulated) application in young B-deficient almond trees grown under a controlled environment. B movement within the plant in relation to the leaf gas exchange, water relations parameters, and root hydraulic conductance was measured. Also, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…According to the B concentration found in the leaves of sweet potatoes tested in the present study, it was observed that it was higher after B application, but to a extent when B was supplied in a nanoencapsulated form. This effect has been previously observed in almond trees [24], but these plants were B deficient. The greater penetration and mobility of nanoencapsulated B as compared to the free form observed in previous studies, was related to a higher ease of penetration through the epidermis facilitated by nanovesicles [23].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…According to the B concentration found in the leaves of sweet potatoes tested in the present study, it was observed that it was higher after B application, but to a extent when B was supplied in a nanoencapsulated form. This effect has been previously observed in almond trees [24], but these plants were B deficient. The greater penetration and mobility of nanoencapsulated B as compared to the free form observed in previous studies, was related to a higher ease of penetration through the epidermis facilitated by nanovesicles [23].…”
Section: Discussionsupporting
confidence: 81%
“…This was also observed with the NIPs (NIP1;2, NIP1;3; NIP4;1, NIP4;2, NIP5;1, NIP6;1, and NIP7;1), which only increased in expression with encapsulated B. Therefore, the results could be associated with the decreased mobility of free B into leaves, as compared with encapsulated B [24]. Therefore, the encapsulated B applied to in vitro plants produced changes in the expression related to B, though only when B was able to penetrate and be transported into the leaf tissues.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…According to the potential toxicity, new types of nanoencapsulations have been used due to their characteristics as hydrophobic vesicles obtained from biological materials. Nanoencapsulations from agricultural by-products have been tested in different crops, with interesting results observed in terms of bioavailability, compatibility, and efficiency as nutrient nanocarriers [13][14][15], without generating waste or leading to the accumulation of toxic elements in the ecosystem. In this way, the biodegradability of the coating reduces environmental impact and any risk of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Given the essentiality of those proteins in the optimization of existing natural resources, their regulation should occur according to the availability of water and nutrients, which ultimately depends on soil availability and structure. On the other hand, the application of foliar fertilization has been proven to modify the expression of aquaporins at the whole-plant level, and its regulation seemed to be essential in improving water and nutrient immobilization when micronutrients were applied using nanovesicles [15].…”
Section: Introductionmentioning
confidence: 99%